Turning efficiency prediction for skid steering via single wheel testing - Flippo, Daniel; Miller, D. P. (My University, 2014)
Wheel design can be enhanced through experimentation, testing, and iteration. Unfortunately, the time and money needed to test full vehicles is costly. A cheaper, less conflated alternative could be to incorporate single wheel testing. The algorithm discussed in this paper uses sinlge wheel testing to predict the full vehicle performance in a skid steer turn. With this prediction algorithm, skid steering can be easily enhanced by iterating on the design of a single wheel without the cost of vehicle testing. To validate this algorithm and explore skid steering enhancement several single wheel skid steering experiments were done and the results were compared to a full vehicle's turning performance.
Keywords: Skid Steer; Robotics; Wheel to soil; Terrain; Single wheel testing